Rousseau and his child-centered, anticultural education | Rousseau e sua educação infantocêntrica e anticultural - Vitorino, Artur José Renda; Pires, Pedro Serafim Anes; Brogiato, Renato Griecco (Revista de Educação PUC-Campinas, 2020)
This article intends to expose how J.J. Rousseau, in his Emile, adopts the assumption that liberty is a natural given, thus something innate in men and intact in children. That being so, a pedagogue who wishes to educate starting from this assumption – that liberty is a natural given – and seeking for virtue would only find it much later, and perhaps only through artifices such as stating that it is God’s will that makes man virtuous. In doing so, even after convincing us that it is not possible to educate without reference to values accepted by one’s cultural tradition, Rousseau fails to show how cultural tradition is transmitted, or even how cultural tradition could be renovated and employed as basis for further development of cultural traditions. As an effect of this first rejection and future, late acceptance (and even during epochs posterior ethical transcendence), Rousseau established the separation between educational and cultural fields, a separation whose ultimate, broad implication is the commonly accepted idea of anticultural education along with child-centered education.